2023
DOI: 10.1111/os.13725
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Full Endoscopic Lumbar Discectomy for Symptomatic Adjacent Segment Disease after Lumbar Fusion in Elderly Patients

Abstract: Purpose Treatment of adjacent segment disease (ASD) is still controversial. The aim of this study was to evaluate the short‐term efficacy and safety and to analyze the technical advantages, surgical approach, and indications of percutaneous full endoscopic lumbar discectomy (PELD) in the treatment of ASD after lumbar fusion in elderly patients. Methods A retrospective of 32 patients with symptomatic ASD were accepted for PELD from October 2017 to January 2020. All patients used the transforaminal approach and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Of the patients with ASD, 87.15% (34/39) showed excellent and good clinical outcomes at final follow-up, which is akin to the rate of 90.63% (29/32) in the study of Feng and others. 16 All measured indexes exhibited statistically significant improvements in all follow-up sections compared to preoperative scores. Previous research has explored the application of variable treatment for ASD following lumbar fusion.…”
Section: Discussionmentioning
confidence: 81%
“…Of the patients with ASD, 87.15% (34/39) showed excellent and good clinical outcomes at final follow-up, which is akin to the rate of 90.63% (29/32) in the study of Feng and others. 16 All measured indexes exhibited statistically significant improvements in all follow-up sections compared to preoperative scores. Previous research has explored the application of variable treatment for ASD following lumbar fusion.…”
Section: Discussionmentioning
confidence: 81%
“…PELD treats almost all types of LDH. 28 , 29 , 30 , 31 The authors Dewin and others found that among a younger group of patients, the outlook for patients who underwent surgery for occult or herniated lumbar disc herniation was significantly better than for those with contained lumbar disc herniation. 32 However, the criteria for classification in their research were not concrete enough.…”
Section: Discussionmentioning
confidence: 99%